THE ROLE OF CLIL IN STEAM EDUCATION IN UZBEKISTAN: BRIDGING LANGUAGE AND INNOVATION FOR SUSTAINABLE DEVELOPMENT (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Content and Language Integrated Learning (CLIL) has emerged as a transformative pedagogical approach that combines content mastery with language acquisition. In Uzbekistan, where educational reforms prioritize global competitiveness and technological advancement, integrating CLIL into STEAM (Science, Technology, Engineering, Arts, and Mathematics) education offers a strategic pathway to cultivate bilingual, critical-thinking professionals. This article explores the synergies between CLIL and STEAM in Uzbekistan’s educational landscape, analyzing current practices, challenges, and opportunities. By fostering interdisciplinary learning and linguistic proficiency, CLIL-enhanced STEAM education aligns with national goals to drive innovation and sustainable development. Recommendations for policy, teacher training, and curriculum design are discussed.